Enhancing the Value of Coffee Husks as Organic Fertilizer in Windu Sari Farming Group, Batukaang Village, Kintamani Bangli - Situmeang, Yohanes Parlindungan; Sudita , I Dewa Nyoman; Swedi, I Komang; Nahak, Stefanus; Rematwa, Haris; Damayanti, Ni Luh Putu Sulis Dewi (Asia Pacific Network for Sustainable Agriculture, Food and Energy (SAFE-Network), 2023)
Coffee Husks produced from coffee processing are waste that can be used as raw material for making organic fertilizer. Utilizing coffee Husks as organic fertilizer can increase added value and farmers' income while reducing the smell from piles of coffee Husk waste, which can pollute the environment. Development efforts to overcome this problem include processing coffee Husk waste into compost. In this service activity, partners will be introduced to and trained in the technology for making quality compost fertilizer and managing coffee farming businesses to provide added value and improve the farmer's economy. This service aims to increase the added value (value added) of coffee Husk waste as organic fertilizer in the Windu Sari Farming Group. The problems found in farmer groups are the problem of piles of coffee husk waste, which have not been appropriately handled, and the problem of technology for making compost fertilizer, which has not been fully understood by partners, as well as farming business management problems related to group strengthening. The method used in community service in Batukaang Village is the Participatory Action and Learning System (PALS). This method aims to make the partner group an object in service activities through various forms such as education, training, counseling, as well as coaching and mentoring. The PALS method is implemented in several stages: (1) awareness phase, (2) capacity building phase, mentoring phase, and (3) institutionalization phase. The results obtained from this service program are in the form of a technology package for making compost fertilizer. From the service that has been carried out in the form of counseling, training, and the practice of making organic fertilizer compost, the response from the community, in this case, the Windu Sari Farmers Group, has been excellent. The participants' enthusiasm was seen from the many questions submitted to the service team regarding compost-making technology and its benefits for agriculture.